Outcome Of Children With Intoxication Or Poisoning- A study from tertiary care hospital - PORWAL, NARENDRA; DANTE, RITHIKA (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To examine the clinical profile and result of youth poisioning and intoxication. Objective: To contemplate the center epidemiological profile and result of youth poisioning at KIMS, Karad. Methods: Retrospective observational study. Setting: peadiatric wards and pediatric emergency unit of Krishna Institute of Health Sciences, Patients conceded with history of ingestion of toxin or intoxication from April 2018 to March 2019. Clinical history was taken in detail with reference to the nature of poisoning, time lapse between consumption and reporting to the hospital, symptomatology and treatment given prior to reporting to the hospital. The children were examined in detail and the findings were recorded as per the Performa prepared.. Results: There were 150 children enrolled in study. Male: female ratio was 1.5:1. The mean age of presentation was 5.3 years. Among 150 patients, the number of cases were more in the age group of 1-3 years. Childhood poisoning is more common among boys, because they are more active, exploratory, inquisitive, adventurous by nature. More number of cases were from low SES group compared to middle SES group. More number of cases were seen in children of illiterate parents and the number of cases decreases as the educational status of the parents improves. Less number of cases was brought to the hospital within 1 hour and majority of cases were brought between 2-5 hours duration. Children from rural areas are at a higher risk of getting poisoned due to organo-phosphorus compounds and snake bites.Most cases, particularly rural children were brought late to the hospital. Though the majority of cases stayed for 1-2 days in the hospital,the average duration of stay in case of snake biteand organo-phosphorus compound poisoningwas more than 4 days. Mortality rate was 0.83% in the present study.